Impact of a Maternal Prevention of Mother-to-child Transmission of HIV (PMTCT) Intervention on HIV-exposed Infants in Uganda - Anays Murillo, MPH; Mary Bachman DeSilva, ScD; Lora L. Sabin, PhD; Nafisa Halim, PhD; Harriet Chemusto, MS; Philip Aroda; Julia Gasuza; Davidson H. Hamer, MD; Anna Larson Williams, MPH; Barbara Mukasa, MD; Lisa J. Messersmith, PhD; Rachael Bonawitz, MD (Global Health and Education Projects, Inc., 2020)
Background: Uganda has successfully reduced pediatric HIV infections through prevention of mother-to-child transmission of HIV (PMTCT) programs, yet little is known about adherence to infant-specific components of interventions. We hypothesized that infants born to mothers receiving the WiseMama (WM) electronic drug monitoring (EDM)-based adherence intervention would have increased uptake of six-week post-natal nevirapine (NVP) infant prophylaxis and better adherence to six-week early infant diagnosis (EID) HIV testing. Methods: At two sites in Uganda, the Wise Infant Study (WIN) prospectively followed an infant cohort. Infants were born to women enrolled in an RCT testing the effect of real-time reminders delivered via EDM on maternal adherence to antiretroviral therapy. We assessed intrapartum and discharge receipt of NVP prophylaxis using pharmacy and infant HIV DNA testing laboratory data. Results: Of 121 women eligible for WIN, 97 (80%) consented and enrolled; 46 had been randomized to control and 51 to intervention. There were no differences in receipt of a six-week NVP supply (control 87%, intervention 82%, p = 0.53). Receipt of any NVP prophylaxis did not vary by delivery location (p = 0.35), and although 12% of infants were delivered at non-study health facilities, they were not less likely to receive NVP at discharge (p = 0.37). Among infants with a completed HIV test, there was no difference in mean time to first test (control 52 days (SD 18), intervention 51 days (SD 15), p = 0.86). Only one infant, in the control group, tested positive for HIV. Conclusion and Global Health Implications: We found no significant differences in adherence to infant PMTCT practices between intervention and control infants with relatively high rates of NVP receipt albeit with suboptimal adherence to six-week EID testing. Further work is needed to ensure improved access, uptake, and follow-up of HIV-exposed infants in the Option B+ era. Key words: • Prevention of maternal to child transmission of HIV • HIV • Nevirapine • Antiretroviral therapy prophylaxis • Early infant diagnosis • HIV-exposed infants   Copyright © 2020 Murillo et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.